The Insecticide Imidacloprid Promotes Algal Growth in Absence of Zooplankton - Lozano, Verónica Laura (2025)
Imidacloprid, a systemic neonicotinoid insecticide, exerts its neurotoxic effects by binding to nicotinic acetylcholine receptors in the central nervous system. In this study, we examined the effects of commercial imidacloprid formulations on the growth of Chlorella vulgaris and other algal species, comparing these responses with those induced by plant hormones. Our results demonstrate that formulated imidacloprid stimulates C. vulgaris growth at concentrations as low as 7.82 μM, with a more pronounced effect than certain phytohormones. We observed similar growth-enhancing effects in other algal species exposed to imidacloprid. Notably, pure imidacloprid induced equivalent growth responses in C. vulgaris, confirming that the observed stimulation results from the active ingredient itself rather than formulation adjuvants. Given its insecticidal mode of action, potential worst-case aquatic contamination scenarios with imidacloprid may lead to significant increases in algal biomass through both direct (growth stimulation) and indirect (reduction of zooplankton grazing pressure) mechanisms.